A new species of Campylothorax Schött, 1893 (Collembola, Paronellidae) from Brazilian Amazon, with an identification key to the genus - Cipola, Nikolas Gioia; Oliveira, Fábio Gonçalves De Lima (Zootaxa, 2016)
A new species of Campylothorax from Brazilian Amazon is described and illustrated. Campylothorax plagatus sp. nov. resembles another Neotropical species, C. cubanus, by abdomen with two transverse bands and pattern of dorsal chaetotaxy. However, the new species differs by unguis with one unpaired apical tooth, unguiculi III truncate, and abdomen IV with 5+5 posterior central macrochaetae. This is the first species of Campylothorax originally described from Brazilian Amazon. A generic key to the 14 species of Campylothorax is provided.